State Governance in Ukraine: Structural Changes, Problems of Transition to Public Management - PERZHUN, Volodymyr (University Scientific Notes, 2021)
Today, Ukraine is in dire need of changes and reforms that would lead to the optimization and effective management of society and the state. One of such important reforms is the transition from state to public management, and further improvement of the foundations and principles of public management. In the management of the state, where complex processes of transition to public management are taking place, there have always been advanced trends of deepening and expanding publicity in the activities of government institutions. This is the path taken by the "old" countries of Western democracy, as well as the countries of the post-socialist camp, the Baltic republics, which today have successfully joined the EU. Ukraine must follow this path if it tries to become a civilized part of the world. Hence, the system of state management should change dramatically, when the most appropriate in the management structure is an organic combination and effective interaction of public government and local self-government. Even more, the efficiency of civil society itself in the management of public affairs and state structures of power is growing. Socio-economic development and social-power relations at the present stage are already experiencing more and more new changes, both positive and negative. They are becoming very important for the state and society. Being complex and ambiguous, such developments and relations require introduction at the legislative and political levels of new governance systems and structures, which would involve mandatory involvement of the most active representatives of civil society in governance. Note that the period of transition to public management is complex, full of various management problems, requires time and competence of politicians, government, NGOs and more. It is evolutionary in nature, when publicity in governance must develop, and representatives of the branches of government will try to solve the problem of governing the state and society competently, transparently, responsibly, flexibly, openly, socially justly, effectively for the benefit of man as the main social capital.